Dispersal and diversity in experimental metacommunities: linking theory and practice. Issue 9 (2nd May 2016) - Grainger, Tess Nahanni; Gilbert, Benjamin
Abstract : There has been a recent rise in the number of experiments investigating the effect of dispersal on diversity, with many of the predictions for these tests derived from metacommunity theory. Despite the promise of linking observed relationships between dispersal and diversity to underlying metacommunity processes, empirical studies have faced challenges in providing robust tests of theory. We review experimental studies that have tested how dispersal affects metacommunity diversity to determine why shortcomings emerge, and to provide a framework for empirical tests of theory that capture the processes structuring diversity in natural metacommunities. We first summarize recent experimental work to outline trends in results and to highlight common methods that cause a misalignment between empirical studies and the processes described by theory. We then identify the undesired implications of three widely used experimental methods that homogenize metacommunity structure or species traits, and present alternative methods that have been used to successfully integrate experiments and theory in a biologically relevant way. Finally, we present methodological and theoretical insights from three related ecological fields (coexistence, food web and priority effects theory) that, if integrated into metacommunity experiments, could help isolate the independent and joint effects of local interactions and dispersal on diversity, and reveal the mechanisms underlying observed dispersal–diversity patterns. Together, these methods can provide stronger tests of existing theory and stimulate new theoretical explorations. Synthesis Although metacommunity experiments offer a unique opportunity to test classic and emerging theory on the relationship between dispersal and diversity, several common challenges have hindered robust tests of theory. We outline how emerging theory on the invasion criterion, food webs and priority effects could be help clarify when and how dispersal affects metacommunity diversity, and identify when experimental approaches that homogenize metacommunities fail to test existing theory. By forging better links between theoretical and empirical work, we hope to motivate novel and improved experimental approaches to understanding the joint effects of local and regional processes on diversity.